Behaviour and knowledge skill levels of orthopedic surgeons about radiation safety and fluoroscopy use: A survey analysis - Fırat Fidan; Mehmet Ümit Çetin; Cengiz Kazdal; Feyzi Kılıç; Ufuk Özkaya (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to evaluate the behaviour and knowledge skill levels of Turkish orthopedic surgeons about fluoroscopy usage and radiation safety. Methods: The questionnaire, consisting of nineteen questions, was sent to orthopaedic surgeons and requested by a total of 323 surgeons online. The questions were about personal information, training and behaviours related to radiation and fluoroscopy usage, and the use of protective equipment. Results: A total of 277 individuals completed the questionnaire. The answers of 180 surgeons whose working duration was more than 1 year and also who participated in at least one fluoroscopy requiring operation per week, were analysed. 22 (12%) participants answered that they were trained on fluoroscopy usage. Sixty people (33.3%) reported that they did not use any protective equipment regularly. The most commonly used protection methods were lead aprons 123 (68.3%). Thyroid protectors were used by 92 participants (52.1%). There was no significant difference between the groups when comparing the use of protective equipment according to the academic title. Only 19 (10.6%) of the surgeons noted that they used dosimeter regularly, and 15 (83.3%) of them reported that they controlled their dosimeters. Conclusion: In this study, Orthopedic surgeons were found not to be adequately trained about use and risks of fluoroscopy and also not to be equipped about methods for preventing radiation damage. Keywords: Orthopedic surgery, Fluoroscopy, Radiation protection, C-arm, Operating room safety